Caring jacket: health monitoring jacket integrated with the internet of things for COVID-19 patients - Hari Maghfiroh; Daru Kusumastuti; Rebbeka Siswandina Sari; Muhammad Hammam Al-Choiri; Maulana Afif; Ricky Aston Susetyo; Muhammad Ahmad Baballe (Institute of Advanced Engineering and Science, 2023)
One of the policies that have been made by the World Health Organization (WHO) and the Indonesian government during this COVID-19 pandemic, is to use an oximeter for self-isolation patients. The oximeter is used to monitor the patient if happy hypoxia which is a silent killer, happens to the patient. To maintain body endurance, exercise is needed by COVID-19 patients, but doing too much exercise can also cause decreased immunity. That’s why fatigue level and exercise intensity need to be monitored. When exercising, social distancing protocol should be also reminded because can lower COVID-19 spreading up to 13.6%. To solve this issue, the Caring Jacket is proposed which is a health monitoring jacket integrated with an IoT system. This jacket is equipped with some sensors and the global positioning system (GPS) for tracking. The data from the test showed the temperature reading accuracy is up to 99.38%, the oxygen rate up to 97.31%, the beats per minute (BPM) sensor up to 97.82%, and the precision of all sensors is 97.00% compared with a calibrated device.